Flexible Model on Special Education Services in Inclusive Setting Elementary School - Imas Diana Aprilia (Journal of ICSAR, 2017)
This research intends to study the implementation of inclusive education in elementary schools in the district of Bandung in order to create a model for special education services in regular schools. The results of the implementation analysis combined with the results of the literature study used as a basis to design the model of special education services in inclusion settings. The main finding of this study is "Flexible Model on Special Education Services in Inclusive Setting Elementary School”. This model is built in three main foundations, which are Standard Operating Procedures (SOPs), guidelines for the implementation in Elementary school in the form of eight National Education Standards (NES), and the principle of the model implementation, namely flexibility